PENGELOLAAN PROGRAM EKSTRAKURIKULER DI SEKOLAH DASAR NEGERI 005 BINUANG KECAMATAN BANGKINANG KABUPATEN KAMPAR - Heri Heri; Zulfan Saam; Isjoni Isjoni (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2019)
This research aims to know (1) Planning of extracurricular activities at Public Elementary School 005 Binuang of Bangkinang Sub-district, (2) Organizing extracurricular activities at Public Elementary School Negeri 005 in Binuang, Bangkinang District, (3) Implementation of extracurricular activities at Public Elementary School 005 Binuang, Bangkinang District, (4) Evaluation of extracurricular activities at Public Elementary School 005 Binuang, Bangkinang District, and (5) Inhibiting factors of extracurricular activities at Public Elementary School 005 Binuang, Bangkinang District. This research uses a qualitative approach using descriptive method. Data collection techniques in this study through through observation, interviews, making field notes, observation, and documentation. The data analysis procedure uses a qualitative descriptive analysis strategy model and a qualitative verificative analysis strategy model. Based on the result of the research, it can be concluded that (1) In making the extracurricular activity, the principal holds a meeting together with the teacher and the committee. Then the principal makes the decree shown to the teacher who is given the task as an extracurricular coach who has expertise in the extracurricular field and authorizes (2) The principal together with the extracurricular instructor facilitates the governing structure led by the headmaster directly and assisted by other teachers as the supervisor of the activity, (3) The implementation of this extracurricular activity is done at the school yard involving all the students Selecting their preferred extracurricular activities, (4) In evaluating the principal to assess the outcomes of the extracurricular in the form of student-owned personality and student achievement as a result of their participation in extracurricular activities, and (5) T extracurricular activities such as low student motivation to follow extracurricular activities and low support of parents to children to follow this activity.